Abbas qui et scriptor? The Handwriting of Robert of Torigni and His Scribal Activity as Abbot of Mont-Saint-Michel (1154–1186). (2014) - Pohl, Benjamin
Abstract : This article investigates a specific twelfth-century hand that occurs in a group of manuscripts connected to the Norman abbey of Mont-Saint-Michel and identifies it as the hand of Robert of Torigni, the famous Anglo-Norman historian who became abbot of that monastery in 1154. The manuscripts used as evidence all contain corrections and interlinear glosses in what I contend constitutes Robert's own hand, and have neither been studied comparatively nor had their relationships scrutinized. Indeed, scholarship to date has actually argued for different examples of handwriting altogether as belonging to Robert and has not inquired as to whether the glosses and annotations contained within the codices discussed here could be indicative of Robert's scribal activity in the scriptorium of Mont-Saint-Michel during the period of his abbacy (1154–86). This article, therefore, seeks to challenge the prevailing notions concerning Robert's characteristic handwriting, both in terms of its supposed shape and character, and with regard to the manuscripts in which it is thought to survive. This fundamental reassessment of previous scholarship will be achieved by combining, for the first time, a comprehensive paleographical analysis of the manuscripts with a discussion of their broader historical and institutional contexts. Furthermore, and perhaps more significantly, in identifying Robert's hand and the contexts in which it survives, this article aims to enhance our knowledge concerning the person behind the script. It will present new and important insights into Robert's activities as head of his monastic community, as well as into his methods as a monastic historian who, as will be shown, was intimately involved in the processes of manuscript production at Mont-Saint-Michel during the second half of the twelfth century. Ultimately, this article argues that Robert, despite being the author and intellectual architect of complex and influential historical works, had in fact very little training as a book scribe, which is evidenced by his handwriting.